Modelli semplificati di analisi delle sorgenti di rischio e del sovraccarico biomeccanico nel settore artigiano: esperienze applicative nei pasticceri, pastai e pizzaioli / Simplified models for analysis of sources of risk and biomechanical overload in craft industries: practical application in confectioners, pasta and pizza makers - Placci, M.; Cerbai, M. (La Medicina del Lavoro, 2011)
«Simplified models for analysis of sources of risk and biomechanical overload in craft industries: practical application in confectioners, pasta and pizza makers». Background: The food industry is of great importance in Italy; it is second only to the engineering sector, involving about 440,000 workers. However, 90% of the food businesses have less than 10 employees and are exempt from legal obligation to provide a detailed Risk Assessment Document. Objectives: The aim of the study was to identify the inconveniences and risks present in the workplaces analyzed with particular reference to biomechanical risk of the upper limbs and the lumbar spine. Methods: This preliminary study, carried out by using pre-mapping of the inconveniences and risks (5) and the “mini-checklist OCRA” (4), involved 15 small food businesses: ovens for baking bread, pastry shops, pizzerias and the production of “Piadina” (flat bread). Results: Although undoubtedly with differences, confectioners, pasta makers, pizza makers and “piadinari” were exposed to similar risks. By analyzing the final graphs, action areas can be identified on which further risk analysis can be made. Conclusions: Exposure is mainly related to repetitive movements, manual handling of loads and a common occurrence is the risk of allergy to flour dust. There are real peaks in demand from customers, that inevitably increase work demands and consequently biomechanical overload. In future studies it will be interesting to investigate this aspect by studying the variations in work demand and the final exposure index of the working day.